(untitled) (Journal of Geography and Environmental Management, 2016)
Dust and sand storms are common dangerous weather phenomenon in arid and semi-arid regions of Kazakhstan, especially in its southern parts with a great variety of desert types and are a powerful source of mineral and salt aerosols. The dust and sand storms aredistributed in Kazakhstan unevenly, depending on the geological structure, wind speed and soil texture. In this study was used long-term meteorological data on dust storms recurrence and their regional division in Kazakhstan. On the basis of generalization and analyses of the numerous cartographic materials, meteorological observations, we identified the powerful sources of dust storms. The regions in Kazakhstan with the highest frequency of dust and sand stormsis Aral Sea region (Aralkum and Kyzylkum deserts). The most active source of dust and sand storms is located in sandy deserts or in areas, which have suffered from human economic activity. They are particularly dangerous for the environment and have a great negative impact on soil conditions.